Peran Guru dalam Meningkatkan Motivasi Belajar Peserta Didik di Sekolah Dasar - Rachmat Nur S S; Khoirul Alif P; Bintang Renaul S; Gilang Praja M (Universitas PGRI Madiun, 2026)
This article discusses the role of teachers in enhancing the learning motivation of elementary school students. Learning motivation is a key factor that determines students' engagement, persistence, and academic achievement, yet many students still show low enthusiasm for learning. Using a literature review method, this study examines how teachers function as motivators, facilitators, classroom managers, and evaluators in the teaching and learning process. The findings indicate that teachers can strengthen student motivation through varied and interactive teaching strategies, a supportive classroom climate, meaningful feedback, rewards, and attention to students' individual characteristics. However, teachers also face challenges such as differences in student characteristics, limited facilities, and low parental involvement. This study concludes that the teacher's role is central and cannot be replaced by learning media alone, so continuous improvement of teachers' pedagogical competence is needed to sustain students' motivation to learn.